The Role of High-Frequency Ultra Sound (HFUS) in Skin Malignancy: A Literature Review - Salamah, Faradina; Maylita Sari; Muhammad Yulianto Listiawan (Journal of Pakistan Association of Dermatologists, 2025)
High-frequency ultrasound (HFUS) has a significantly reduced tissue penetration depth that provides superior resolution images of tissues and structures near the skin’s surface. HFUS is one of the examinations that can be performed to assess skin tumours before and after biopsy or surgery, even after therapy. The utilization of HFUS in skin malignancies covers diagnosis, staging and treatment phases. HFUS provides information about tumour features such as size, shape, depth, consistency, and vascularity, that can be done before an invasive skin biopsy or surgery. HFUS is a supporting examination and a non-invasive tool to plan the treatment of certain skin tumours. In addition, HFUS can assess prognosis in some cases that require additional management. The final diagnosis of skin tumour types is not completely feasible by using the HFUS, because it is unable to distinguish between benign and malignant tumours. Another limitation is that it cannot give tissue diagnostics. HFUS cannot discriminate between tumour and inflammatory infiltrates, which may result in overestimation of tumour dimensions. It is important to emphasise that HFUS should not be utilised as a standalone diagnostic tool, but rather in conjunction with clinical examination and histopathological findings to help reach a definite diagnosis and treatment approach